Aplikasi Biokanat Guna Memperbaiki Sifat Kimia dan Menanggulangi Kontaminan Merkuri di Tanah Bekas Tambang Emas - Gusmini Gusmini; Adrinal Adrinal; Feri Arlius; Elsa Lolita Putri (Institut Pertanian Bogor, 2024)
Gold mining is an activity that utilizes natural resources by extracting the economic value of the deposits. Mining activities can produce hazardous pollutants, namely Hg (mercury), which can physically, biologically, or chemically damage soil quality. This study aimed to determine the role of biokanat application on the chemical properties of ex-mining land and to determine the effect of biokanat on reducing Hg levels in Kanagarian Padang Sibusuak, Sijunjung Regency. This study was a field experiment with 3 biokanat treatments (0, 10, and 20 ton/ha) with 3 replicates. The experimental 9 units were allocated based on Randomised Block Design. The data were statistically analyzed using an F-test with a 5% significance level. Then, it was continued using DNMRT if the Fcalculated > Ftable. The results showed that the dose of biokanat 20 ton/ha could increase the soil pH to 6.08, organic-C to 2.4%, P-available to 11.96 ppm, total-N to 0.23%, CEC to 2.58 cmol/kg, the basic cations especially Ca into 3.53 cmol/kg, Mg into 0.37 cmol/kg, K into 0.26 cmol/kg, and Na into 0.29 cmol/kg. Application of biokanat 20 ton/ha reduced the soil mercury (Hg) content to 15.96 ppm. Keywords: biocanat, mercury, gold mining